Fresamento com ar quente: uma proposta para minimizar a formação de trincas térmicas em ferramentas de metal duro - Lima, Ramsés Otto Cunha (2011)
This work presents the results, analyses and conclusions about a study carried out with objective of minimizing the thermal cracks formation on cemented carbide inserts during face milling. The main focus of investigation was based on the observation that milling process is an interrupted machining process, which imposes cyclic thermal loads to the cutting tool, causing frequent stresses changes in its superficial and sub-superficial layers. These characteristics cause the formation of perpendicular cracks from cutting edge which aid the cutting tool wear, reducing its life. Several works on this subject emphasizing the thermal cyclic behavior imposed by the milling process as the main responsible for thermal cracks formation have been published. In these cases, the phenomenon appears as a consequence of the difference in temperature experienced by the cutting tool with each rotation of the cutter, usually defined as the difference between the temperatures in the cutting tool wedge at the end of the cutting and idle periods (T factor). Thus, a technique to minimize this cyclic behavior with objective of transforming the milling in an almost-continuous process in terms of temperature was proposed. In this case, a hot air stream was applied into the idle period, during the machining process. This procedure aimed to minimize the T factor. This technique was applied using three values of temperature from the hot air stream (100, 350 e 580 oC) with no cutting fluid (dry condition) and with cutting fluid mist (wet condition) using the hot air stream at 580oC. Besides, trials at room temperature were carried out. Afterwards the inserts were analyzed using a scanning electron microscope, where the quantity of thermal cracks generated in each condition, the wear and others damages was analyzed. In a general way, it was found that the heating of the idle period was positive for reducing the number of thermal cracks during face milling with cemented carbide inserts. Further, the cutting fluid mist application was effective in reducing the wear of the cutting tools.